Small-Scale Application of Urea Based Selective Non-Catalytic Reduction of Nitric Oxide in Diesel Burning Effluent - Hossain, K. A.; Jaafar, M. N. M.; Ani, F. N.; Mustafa, A. (2003)
Selective Non-Catalytic Reduction (SNCR) of nitric oxide has been studied experimentally injecting different concentrations of aqueous urea solution in a pilot-scale diesel fired tunnel furnace, which was set to run at 3-4% excess oxygen level and was producing low ppm of baseline NOx ranged from 65 to 74 ppm within the investigated temperature range. The furnace simulated small-scale combustion systems such as low capacity boilers, hot water heaters, oil heaters etc., where the operating temperatures are usually in the range of about 900 to 1300 K and baseline NOx emission level remains within 100 ppm. One significant aspect of the study is that it employed commercial grade of urea as NOx reducing agent. The test data showed a significant amount of NOx reduction, which was not pronounced by the previous researchers with urea SNCR for this low ppm of NOx. Variation in concentrations of urea solution has effect on NOx reduction characteristics with residence time, injection temperatures and normalized stoichiometric ratio (NSR). At a particular value of NSR, NOx reduction as well as effective temperature window was observed to be affected at different concentrations of urea flow. At an NSR of 3, a maximum of 51 % reduction was observed using 10% aqueous urea solution at 1128 K, while 25% urea solution achieved only a maximum of 26% reduction. Although the NOx reduction and width of the effective temperature window varied significantly with the variation in solution concentration, the peak temperature of the reduction varied trivially.